Innovative Model for Edutainment-Based Tourism Development (Education and Entertainment) at the Puri Agung Pemecutan Cultural Heritage Site in Denpasar, Bali - I Gusti Ngurah Agung Nugraha Satria Wibawa; Agus Made Yoga Iswara; Denok Lestari (CV. Publikasi Indonesia, 2026)
Puri Agung Pemecutan Denpasar is one of the important cultural heritage sites in Denpasar City that possesses significant historical and cultural values. This study aims to identify the current tourism model implemented at the cultural heritage site of Puri Agung Pemecutan Denpasar, analyze the positive and negative impacts of the existing tourism development, and formulate an innovative edutainment-based (education and entertainment) tourism development model. This study employed a qualitative descriptive approach. Data were collected through field observations, in-depth interviews, documentation, and questionnaires distributed to 30 respondents consisting of site managers, local community members, and visitors. The results indicate that the current tourism model at Puri Agung Pemecutan is still conventional and passive, mainly consisting of site visits, observation of traditional palace architecture, and oral historical explanations delivered by guides. Although this model provides positive impacts such as increasing visitors’ awareness and understanding of the historical and cultural values of the palace and creating opportunities for local community involvement, it still has limitations in terms of interpretation systems and innovative presentation of cultural education. Therefore, this study proposes an innovation of an edutainment-based tourism model through 6 activities called “SAD PESONA”, there are historical and cultural exhibitions, educational cultural performances, interactive historical storytelling, the digital interpretation media observation, historical and cultural documentary narrative, and participatory cultural workshops activation.